PEMANFAATAN ASAP CAIR DARI PELEPAH KELAPA SAWIT UNTUK MENINGKATKAN KUALITAS BAHAN OLAH KARET PETANI KARET - Seri Maulina; Erni Misran; Maya Sarah (Talenta Publisher, 2017)
An effort in improving field latex quality has been conducted through community service activity for rubber farmers at Dusun Alur Hitam, Sekoci Village, Langkat Regency. The farmers generally use unrecommended coagulant such as fertilizer, extract of mengkudu or fern sap for coagulating their latex that can reduce the quality of rubber. The low quality of field latex, thus in turn reduce its selling price and income of farmers. Liquid smoke produced by pyrolysis of palm frond waste was proposed to be used as latex coagulant. Team of community service has designed and manufactured a pyrolysis reactor for this activity. The pyrolysis process produced brown liquid smoke with pH of 3 and a strong smoke smell. The produced liquid smoke can coagulate latex perfectly with the time needed were 2¢,25ʺ; 3¢,21ʺ and 4¢,29ʺ at the ratio of liquid smoke to latex were 1:10, 1:15 and 1:20 respectively with the use of liquid smoke of 2 mL. The dry rubber content of latex reached 73.48%. Thus, the utilization of smoke liquid can improve the dry rubber content as high 20.48% since the rubber buyer agents only set the dry rubber content of 53%. The elongation at break (EB) of latex was in the range of 165.55% - 286.93%. it is necessary to increase the knowledge and skill of rubber farmers. In the future, the establishment of farmer group or cooperative at Dusun Alur Hitam should be encouraged so as to facilitate the farmers in selling their product